MONITORING OF CONTRAST AGENT-INDUCED TOXICITY IN A TERTIARY HEALTH-CARE CENTER - REHMANI, MANTASHA; KHAN, IRFAN AHMAD (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The objective of the study is to monitor radiological contrast agent-induced toxicity in patients and compare the toxicity and safety profiles of different radiological contrast agents. Methods: This is an open-label, prospective, observational study conducted in a tertiary care hospital in April 2021 and September 2021. The study assessed the incidence of contrast-induced adverse events in different radiological procedures, i.e., contrast-enhanced computerized tomography (CECT) scans and contrast-enhanced magnetic resonance imaging (CEMRI). Adverse drug reactions (ADRs) were recorded using the standard central drug standard control organization ADR reporting form. Causality assessment of the ADRs was done using Naranjo’s scale while severity assessment was measured using the Modified Hartwig and Siegel scale. Results: The baseline characteristics of patients were almost similar in both groups. The mean age and gender distribution of the patients were not significantly different among both groups. For the adverse reaction in CECT, the male-to-female ratio was 1.88, and for CEMRI, it was 1.61. The ADRs due to CEMRI and CECT were mild in severity. The results showed that ADRs between contrast-enhanced MRI and contrast-enhanced CT were not significantly different. Conclusion: Based on the results obtained, we concluded that the contrast agents used in the radio-diagnostic procedures are safe, and further research in this field is of fundamental importance.